Phantom pain - etiopathogenesis and treatment methods - Olszak, Joanna; Zalewa, Karolina; Bartoszek, Lidia; Orłowska, Dominika; Kapłan, Wojciech; Poleszczuk, Mikołaj; Czuba, Anna; Poleszczuk, Karol; Milewska, Alicja (Journal of Education, Health and Sport, 2024)
Introduction and Purpose Phantom limb pain (PLP) is a complex and multifactorial phenomenon that arises following limb amputation, affecting a significant number of patients. This study aims to explore the underlying mechanisms of PLP, assess current treatment strategies, and evaluate the effectiveness of various therapeutic interventions, including pharmacological and non-pharmacological approaches. Material and Methods A comprehensive literature review was conducted using the PubMed database, focusing on articles published up to the end of 2023. The search included the keywords: "amputation", "mirror therapy", "pain", "phantom limb", "amputation-induced pain", "chronic pain" in various combinations. Relevant studies were selected based on criteria such as the etiopathogenesis of phantom pain and its treatment methods. Results The findings indicate that PLP is associated with both peripheral and central nervous system changes, influenced by individual risk factors such as genetics and psychological state. Therapeutic interventions such as mirror therapy, graded motor imagery, and neuromodulation have shown promise in alleviating symptoms, although the evidence for their effectiveness remains variable. The implementation of a multidisciplinary approach significantly improves outcomes in managing PLP. Conclusions Effective management of phantom limb pain requires a comprehensive understanding of its etiology and a tailored treatment strategy that incorporates both pharmacological and non-pharmacological methods. Future research should focus on establishing robust clinical protocols and long-term efficacy studies to enhance the quality of life for individuals suffering from PLP.